Legal Development in Post-Covid-19 Environmental Friendly Medical Waste Management Efforts through Local Wisdom - Aris Setyawan; Azzahra Mutiara Ayu (Journal of Legal and Cultural Analytics, 2022)
Treatment of medical waste if not done properly will pose a potential hazard to health and the environment. Special treatment and facilities are needed since the waste is generated (from the cradle) until it is destroyed (to grave). Efforts to develop environmental law, especially post-Covid-19, are needed by developing the potential of local wisdom through policies to prevent environmental damage. The purpose of this research is to find out the obstacles and efforts that must be made by the government in post-Covid-19 medical waste management through local wisdom. This research method is a literature study by examining reference sources as secondary data. The results of the study show that there are still obstacles in post-Covid-19 medical waste management through local wisdom, so it is necessary to collaborate with the government with the private sector and the community in realizing environmentally friendly post-Covid-19 medical waste management.